Uterine Didelphys with Transverse Vaginal Septum – A Complex rare Müllerian Anomaly - Khan, Dina Aisha; Sharma, Nalini; Saha, Anusmita; Das, Rituparna; Panda, Subrat (Acta medica Lituanica, 2021)
During the development of the female genital tract, any insult to the normal development process results in a set of intriguing abnormalities known as Müllerian duct abnormalities. The uterine didelphys is the second least common type of anomaly among these, which may commonly be associated with a longitudinal vaginal septum (lateral fusion defect). However uterine didelphys along with a transverse vaginal septum (lateral fusion plus resorption defect) is a very rare finding and to the best of our knowledge, thecase that we hereby report is the second one in literature. A 16-year-old unmarried girl presented with primary amenorrhoea and cyclical pain for 18months.On clinical examination and imaging, a case of uterine didelphys and transverse vaginal septum was found. Her urinary tract was normalon USG and MRI evaluation. Excision of the septum was done by abdomino-vaginal approach. The patient was discharged well. We conclude that a patient presenting with primary amenorrhea especially with cyclical dysmenorrhea with a transverse vaginal septum on examination should be thoroughly investigated for associated upper genital tract abnormalities as the treatment strategy and prognosis is largely dependent on the correct classification of the anomaly.